A New Defoliator of Ceiba pentandra (L.) Gaertn. from Tamil Nadu, India - Thakur, M. L.; Madhavan Pillai, S. R. (Indian Forester, 1984)
Pericallia ricini Fabr. is recorded as new pest for Ceiba pentandra, from Tamil Nadu. Feeding habit, enemy complex and control measures have been discussed.